Jump serve performed by volleyball players of different qualifications - Alina Melnyk; Tamara Liakhova (Pedagogy of Health)
Background and Study Aim. An important component of volleyball competitive activity is to obtain statistics on the performance of the jump serve. This allows the coach to decide on the appropriateness of its use in different moments of the game to obtain optimal results. The purpose of the work is to determine the indicators of the effectiveness of jump serve by volleyball players of student teams.